Islamic political supports and voting behaviors in majority and minority muslim provinces in Indonesia - Delmus Puneri Salim (Indonesian Journal of Islam and Muslim Societies, 2022)
This article focuses on relation between Islam and politics in Indonesia during the last two presidential election. The article looks at Islamic political support to Prabowo Subianto and its influence into the 2014 and 2019 Presidential election in the majority and minority Muslim provinces. Data collection was conducted by document study to texts of internet media, especially on the issues of Islamic political support to Prabowo Subianto and results of the 2014 and 2019 Presidential election in the chosen majority and minority Muslim provinces. This study reveals correlation between Islam and politics with results of the two previous Indonesian Presidential election, finding out that the Islamic political support has increased votes of the promoted candidates in majority Muslim provinces and reversely decreased votes of the candidate in minority Muslim provinces. The study shows that the Islamic political supports affect voting behaviors more in minority Muslim provinces than in majority Muslim provinces. These findings, in turn, highlight the importance of developing a strategy to manage religious political support in Indonesian elections.